Three-Phases Interface Induced Local Alkalinity Generation Enables Electrocatalytic Glucose Oxidation in Neutral Electrolyte - Chen, Yangru; Zhang, Jun; Ding, Zhenyao; Chen, Liping; Wang, Haili; Zhang, Man; Feng, Xinjian (Frontiers in Bioengineering and Biotechnology, 2022)
Electrocatalytic glucose oxidation is crucial to the development of non-enzymatic sensors, an attractive alternative for enzymatic biosensors. However, due to OH− consumption during the catalytic process, non-enzymatic detection generally requires electrolytes having an alkaline pH value, limiting its practical application since biofluids are neutral. Herein, via interfacial microenvironment design, we addressed this limitation by developing a non-enzymatic sensor with an air–solid–liquid triphase interface electrodes that synergistically integrates the functions of local alkalinity generation and electrocatalytic glucose oxidation. A sufficiently high local pH value was achieved via oxygen reduction reaction at the triphase interface, which consequently enabled the electrochemical oxidation (detection) of glucose in neutral solution. Moreover, we found that the linear detection range and sensitivity of triphase non-enzymatic sensor can be tuned by changing the electrocatalysts of the detection electrode. The triphase electrode architecture provides a new platform for further exploration and promotes practical application of non-enzymatic sensors.